2003
DOI: 10.1128/iai.71.8.4432-4440.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complement Component C3 Deficiency on Experimental Lyme Borreliosis in Mice

Abstract: Mice deficient in complement component C3 (C3؊/؊ ) and syngeneic C57BL/6 control mice were challenged with Borrelia burgdorferi to determine the role of complement in immune clearance and joint histopathology during experimental Lyme borreliosis. Tibiotarsal joint, ear, and heart tissues were monitored for spirochete numbers at 2, 4, 8, and 12 weeks postinoculation with 10 5 B. burgdorferi B31 clone 5A4 by using quantitative real-time PCR. The spirochete load in joint and ear tissue remained higher in the C3 ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 54 publications
6
39
0
Order By: Relevance
“…Experiments in which added C5a increased the number of Ag-specific effector T cells in vitro and anti-C5 mAb decreased the number in vivo suggested that C5a could influence the strength of the induced T cell response (9). Consistent with this, published work by Sacks (10 -14), Carroll (10,(15)(16)(17), and by our group (9) have shown that C3 or factor D deficiency limits T cell expansion following exposure to viruses (16,18,19), bacteria (20,21), autoantigens (17), and alloantigens (10 -14, 22).…”
supporting
confidence: 56%
“…Experiments in which added C5a increased the number of Ag-specific effector T cells in vitro and anti-C5 mAb decreased the number in vivo suggested that C5a could influence the strength of the induced T cell response (9). Consistent with this, published work by Sacks (10 -14), Carroll (10,(15)(16)(17), and by our group (9) have shown that C3 or factor D deficiency limits T cell expansion following exposure to viruses (16,18,19), bacteria (20,21), autoantigens (17), and alloantigens (10 -14, 22).…”
supporting
confidence: 56%
“…Likewise, mice lacking the B cell complement receptors CD21 and CD35 are not impaired in the host response to B. burgdorferi infection and even produce increased levels of Ag-specific IgM (64). However, infection of C3-deficient mice with larger numbers of B. burgdorferi produce the opposite result (65). Signaling through CD1d has also been proposed to explain how this molecule enhances MZ B cell production of B. hermsii-specific Ab (38).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that MyD88-independent events facilitate recruitment of inflammatory cells into the joint tissue. Possible contributors to this response include localized production of chemokines (57), localized activation of complement (58), or release of chemotactic peptides by the invading bacterium.…”
Section: Discussionmentioning
confidence: 99%